2020
DOI: 10.1080/2162402x.2020.1832324
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness and robustness of Immunoscore for personalized management of cancer patients

Abstract: This review details the analytical performance characteristics of the consensus Immunoscore, measuring the immune response to cancer, improving the estimation of risk of recurrence, and predicting response to treatment for patients with colon cancer. The analytical validation of Immunoscore has been documented. Immunoscore is a robust, reproducible, quantitative, and standardized immune assay, with a high prognostic performance, independent of all of the prognostic markers currently used in clinical practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The analytical validation of IS has been demonstrated previously [ 20 , 25 ]. Immunoscore ® was deemed to be a robust, reproducible, quantitative, and standardized immune assay, with a high prognostic performance, independent of all of the prognostic markers currently used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical validation of IS has been demonstrated previously [ 20 , 25 ]. Immunoscore ® was deemed to be a robust, reproducible, quantitative, and standardized immune assay, with a high prognostic performance, independent of all of the prognostic markers currently used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor immune microenvironment is one of the research hotspots in recent years ( 28 , 29 ). The concept of Immunoscore provides a new direction and a strong guarantee for the evaluation of various tumors ( 30 33 ). Increasing studies have shown that the density of CD3 + and CD8 + lymphocyte populations in the tumor microenvironment could effectively predict the recurrence and metastasis of GC and complement the TNM staging system ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor immune microenvironment is one of the research hotspots in recent years (28,29). The concept of immunoscore provides a new direction and a strong guarantee for the evaluation of various tumors (30)(31)(32)(33). Increasing studies have shown that the density of CD3 + and CD8 + lymphocyte populations in the tumor microenvironment could effectively predict the recurrence and metastasis of GC and complemented the TNM staging system (34,35).…”
Section: Discussionmentioning
confidence: 99%